2006
DOI: 10.1103/physrevb.73.134102
|View full text |Cite
|
Sign up to set email alerts
|

Different incommensurate composite crystal structure for Sc-II

Abstract: The long uncertain crystal structure of the high-pressure phase of scandium, Sc-II, is found to have an incommensurate composite structure comprising a body-centered host structure and a C-face-centered guest structure. At 23 GPa, the shortest distance between guest atoms is ϳ2.7 Å, comparable to the average hosthost distance of 2.8 Å. This differs from the structure proposed recently ͓H. Fujihisa et al., Phys. Rev. B 72, 132103 ͑2005͔͒ which has a body-centered guest structure, with anomalously short guest-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 13 publications
5
52
0
Order By: Relevance
“…19 near here…] A comprehensive review by McMahon and Nelmes [351] categorizes the complex structures into four types: incommensurate composite structures, incommensurate modulated structure, modulated layer structures, and other complex structures. Incommensurate composite structures comprise of two interpenetrating components, a 'host' and a 'guest', which are incommensurate with each other along one or more axes, e.g., in Ba [352], Sr [353], Rb [354], Sb [355,356], and Sc [357]. Incommensurate modulated structure can be viewed as a basic structure with the atoms displaced by a modulation wave, which is incommensurate with the basic unit cells.…”
Section: Hp Crystallographymentioning
confidence: 99%
“…19 near here…] A comprehensive review by McMahon and Nelmes [351] categorizes the complex structures into four types: incommensurate composite structures, incommensurate modulated structure, modulated layer structures, and other complex structures. Incommensurate composite structures comprise of two interpenetrating components, a 'host' and a 'guest', which are incommensurate with each other along one or more axes, e.g., in Ba [352], Sr [353], Rb [354], Sb [355,356], and Sc [357]. Incommensurate modulated structure can be viewed as a basic structure with the atoms displaced by a modulation wave, which is incommensurate with the basic unit cells.…”
Section: Hp Crystallographymentioning
confidence: 99%
“…These structures, found first in barium (Ba) [1], and then in an abundance of other group 1, 2, 3, and 15 elements [2][3][4][5][6][7][8][9][10][11][12], and which are also predicted to occur in other elements at extreme pressures [13], comprise a tetragonal (or monoclinically distorted) host structure with channels running along the c axis. Located within these channels are one-dimensional (1D) chains of guest atoms, which order into a number of different structures.…”
Section: Introductionmentioning
confidence: 99%
“…These calculations also showed that the hcp phase is competitive with the pseudoBa-IV phase and one could expect that elements with the hcp structure because of partial sd-hybridized bonding might undergo a transition to a composite phase at high pressures. Indeed, the Sc-II phase, which was unknown for a long time, has been recently determined as an incommensurate host-guest structure, isostructural to Sr-V phase (9). The structural changes are accompanied also by drastic changes of the transport properties with pressure.…”
mentioning
confidence: 99%